Ferrocene Analogues of Hydrogen-Bond-Donor Catalysts: An Investigative Study on Asymmetric Michael Addition of 1,3-Dicarbonyl Compounds to Nitroalkenes - Rao, Kadiyala Srinivasa; Trivedi, Rajiv; Kantam, M. Lakshmi (Synlett, 2015)
This report describes the synthesis of eight ferrocene derivatives of squaramide- or thiourea- based bifunctional catalysts containing cinchona alkaloid moieties. A stepwise sequential route was used to assemble the various components of these ferrocene derivatives. The resulting bifunctional catalysts were used successfully in asymmetric Michael additions of 1,3-dicarbonyl compounds to β-nitrostyrenes. The corresponding products were obtained in high yields and in good to excellent enantioselectivities and diastereoselectivities under mild conditions by using 1 mol% of the catalyst.
Keywords: Michael additions; asymmetric catalysis; ferrocenes; alkaloids; nitro compounds; dicarbonyl compounds